2016
DOI: 10.1590/2317-4889201620160004
|View full text |Cite
|
Sign up to set email alerts
|

A preserved early Ediacaran magmatic arc at the northernmost portion of the Transversal Zone central subprovince of the Borborema Province, Northeastern South America

Abstract: ABSTRACT:Magmatic arcs are an essential part of crust-forming events in planet Earth evolution. The aim of this work was to describe an early Ediacaran magmatic arc (ca. 635-580 Ma) exposed in the northernmost portion of the Transversal Zone, central subprovince of Borborema Province, northeast Brazil. Our research took advantage of several syntheses by different authors, including theses and dissertations, carried out on magmatic rocks of the study area for the last 30 years. The ca. 750 km long and up to 140… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(6 citation statements)
references
References 32 publications
0
4
0
2
Order By: Relevance
“…1 and 2), which are subject of many previous studies. We highlight the last syntheses by Oliveira (2008), , 2014), Van Schmus et al (2011), and Brito Neves et al (2016. Inside this zone that constitutes the Borborema central subprovince, several tectonostratigraphic terranes (besides TAM), polygonal segments of the basement (basement inliers) of the Archean and Paleoproterozoic orogenic constructions are found: Alto Moxotó, Coremas Dam, São José do Caiana, Icaiçara, and São Pedro.…”
Section: Borborema Province and Transversal Zonementioning
confidence: 53%
“…1 and 2), which are subject of many previous studies. We highlight the last syntheses by Oliveira (2008), , 2014), Van Schmus et al (2011), and Brito Neves et al (2016. Inside this zone that constitutes the Borborema central subprovince, several tectonostratigraphic terranes (besides TAM), polygonal segments of the basement (basement inliers) of the Archean and Paleoproterozoic orogenic constructions are found: Alto Moxotó, Coremas Dam, São José do Caiana, Icaiçara, and São Pedro.…”
Section: Borborema Province and Transversal Zonementioning
confidence: 53%
“…Granitic domains are abundant and precisely record distinct stages of the Brasiliano orogeny (pre-, syn-and post-tectonic magmatism), having been intensively investigated for decades (Almeida et al 1967, Sial 1987 1999, Guimarães & Silva Filho 2000, Guimarães et al 2005, Ferreira et al 2003, Neves et al 2006, Brito Neves et al 2016. A review of the overall petrological aspects of the granites can be found in Ferreira et al (1998), Van Schmus et al (2011), and Sial & Ferreira (2016.…”
Section: Borborema Provincementioning
confidence: 99%
“…It comprises the São José do Caiano, Piancó-Alto Brígida, Alto Pajeú, Alto Moxotó, and Rio Capibaribe domains/ terranes. Terrane assembly and plate tectonics processes such as subduction and continental collision have been invoked as responsible for the Neoproterozoic crustal building of this area (e.g., Santos & Medeiros 1999, Kozuch 2003, Medeiros 2004, Santos et al 2010, 2017b, Brito Neves et al 2016, Basto et al 2019, but intracontinental orogenesis is also regarded (Neves 2015).…”
Section: Borborema Provincementioning
confidence: 99%
“…A região em que estão localizados os batólitos e stocks da SISC possui história petrológica complexa (e.g., Oliveira et al, 2010Oliveira et al, , 2017. Os corpos da SISC localizam-se predominantemente no SOS e no Superterreno Pernambuco-Alagoas (STPEAL ;Brito Neves et al, 2016;Brito Neves e Silva Filho, 2019). Davison e Santos (1989) definiram o SOS, anteriormente nomeado de Faixa Sergipana, como um conjunto de terrenos distintos e formados por seis domínios geológicos.…”
Section: Contexto Geológico Regionalunclassified